The moral teaching of Paul selected issues - Furnish, Victor Paul 1931- (Nashville, Tenn. Abingdon Press, 2009)
The sacred cow and the white elephant -- Sex, marriage, and divorce -- Homosexuality -- Women in the church -- The church in the world
The sacred cow and the white elephant -- Sex, marriage, and divorce -- Homosexuality? -- Women in the church -- The church in the world.
Includes bibliographical references and index
Archivierung prüfen
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Ethics in the Bible; Aufsatzsammlung